(untitled) (Research, Society and Development, 2021)
The objective of this study was to determine the chemical composition and apparent metabolizable energy (AME), AME corrected for nitrogen balance (AMEn) and its respective metabolizable coefficients of animal byproducts for broiler chickens with different ages. Meat and bone meal, poultry by-product meal, tilapia processing residue and poultry fat were evaluated. A total of 760 male broiler chickens were used and evaluated and the phases: pre-starter (1 to 8 d of age); starter (11 to18 d); grower 1 (21 to 28 d); grower 2 (31 to 38 d), and finisher (41 to 48 d). Total excreta collection method was performed in five metabolism assays. The experimental design was completely randomized, and data were submitted to analysis of variance, posteriorly, the four feeds were compared by Tukey test and a regression analysis was performed with broiler chickens age. The significance was considered at 5% probability. The values of AME and AMEn were higher in older birds for all ingredients. The lesser CAME and CAMEn were obtained for meat and bone meal, for the regression analysis poultry by-product meal, tilapia processing residue and poultry fat had an increased linear effect with birds age and there was no adjust for meat and bone meal for regression analysis.